Complicating the quantity-quality transition. Issue 3 (2nd October 2021) - Kircz, Joost; van der Linden, Marcel
Abstract : Hegel, Engels and Marx knew that a quantitative reduction or increase of an entity can lead to a change in its nature (quality). The theorisation of this process has made almost no progress since the late nineteenth century. In the present essay we attempt to rethink and refine the notion of a Quantity-Quality-Transition (QQT). Aspects discussed include: the mediation between quantity and quality through 'measure'; the different types of QQT; the (ir)reversibility of QQTs; the stratification of reality (properties that pop-up only at a certain level of complication); transitional phases within QQTs; and whether QQTs are lawful processes or not. We conclude that QQT is an 'umbrella' notion which encompasses many variations and can only be understood by delineating the intricate interplay of multiple (non-linearly interpenetrating) levels of processes.